J. S. Mill’s Fourth Proposition in the Austrian Theory of Economic Cycles - Iorio, Ubiratan Jorge (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In the Fourth Proposition of J. S. Mill, formulated in 1848, the author suggests that the demand of consumer goods and the demand of investments can move in opposite directions, in contrast with modern macroeconomic models, in which the levels of consumption expenditures and of investment move in the same direction. In this article, my purpose is to show the role played by J. S. Mill’s Fourth Proposition in the Austrian Theory of Economic Cycles, in order to compare the Austrian theoretic stance with contemporary macroeconomic streams.